Role of arbuscular mycorrhizal fungi in enhancing soil health and plant resilience - Chandra, Priyanka; Sundha, Parul; Basak, Nirmalendu; Rai, A. K.; Yadav, R. K. (Indian Farming, 2025)
Arbuscular mycorrhizal fungi (AMF) form symbiotic associations with the roots of most terrestrial plants and play a pivotal role in maintaining soil health and ecosystem stability. Through their extensive hyphal networks, AMF enhance plant access to key nutrients particularly phosphorus and nitrogen while receiving carbohydrates in return, thus, supporting a mutualistic exchange. Their role in improving soil structure is mediated by glomalin production, which stabilizes soil aggregates, enhances porosity, and fosters microbial activity. AMF also contribute to organic matter decomposition and carbon sequestration, further influencing nutrient cycling. Importantly, AMF have emerged as effective agents for mitigating salinity stress in plants by improving phosphorus acquisition, reducing sodium uptake, and maintaining optimal K⁺/Na⁺ and Mg²⁺/Na⁺ ratios in plant tissues. Despite observed genotype-dependent variability in AMF effectiveness, their integration into sustainable agricultural practices such as reduced tillage, crop rotation, and inoculation offers a promising strategy for improving soil fertility, minimizing chemical inputs, and enhancing crop resilience under abiotic stress conditions. Understanding the functional mechanisms of AMF is thus vital for leveraging their potential in agroecological systems.